Efficacy of ChatGPT in Human Resource - Yadav , Sangeeta; Gupta , Mahek; Khan , Shariyaz (Recent Advances in Commerce, Management, and Tourism, 2023)
Human resources (HR) of any enterprise plays a substantial role in growth of the organisation by designating competent and skilled employees. For accomplishing its long-term goals, an organization must make human resource contented and pleased. In current scenario, HR services are been integrated through Information Technology (IT) in form of Human Resource Information system (HRIS), HR analytics, etc. Artificial Intelligence has developed an emerging technology in business practices which assists the enterprises to grow at a large scale. The invention of chatbots, a significant domain in AI and NLP, the enterprises have developed more AI centric. AI increasingly forms a vital context for the dispersal of power in workplaces. The technology resolves the complicated problems into simplified solutions. Chatbots facilitates an understanding of AI amongst the employees and influences enterprise decision making process. Therefore, the current study outlines how ChatGPT can redefine the way HR professionals engage with their workforce.